Gender Reassignment Surgery in Human Immunodeficiency Virus-Positive Patients: A Report of Two Cases - Kim, Seok-Kwun; Choi, Ji-An; Kim, Myung-Hoon; Kim, Min-Su; Lee, Keun-Cheol (Archives of Plastic Surgery, 2015)
It is believed that surgery on human immunodeficiency virus (HIV)-positive patients is dangerous and should be avoided due to the possibility of postoperative infection of the patients or HIV occupational transmission to the medical staff. We discuss here the preparations and measures needed to conduct surgery safely on HIV-positive patients, based on our experience. We performed sex reassignment surgery on two HIV-positive patients from January 2013 to January 2015. Both of them were receiving highly active antiretroviral therapy and were asymptomatic, with a normal CD4 count (>500 cells/µL). The HIV-RNA was undetectable within the bloodstream. All the staff wore protective clothing, glasses, and three pairs of protective gloves in the operating room because of the possibility of transmission. Prophylactic antibiotics were administered to the patients, and antiviral therapy was performed during their perioperative course. Neither of the patients had postoperative complications, and none of the medical staff experienced accidental exposure. Both patients had satisfactory surgery outcomes without complications. HIV-positive patients can undergo surgery safely without increased risk of postoperative complications or HIV transmission to the staff through the proper use of antibiotics, active antiretroviral therapy, and supplemental protective measures with post-exposure prophylaxis for the staff in case of HIV exposure.
Keywords: Sex reassignment surgery; HIV infection; Post-exposure prophylaxis